Thermal history of the northern Olympic Domain, Gawler Craton; correlations between thermochronometric data and mineralising systems - Hall, J.; Glorie, S.; Reid, A.; Collins, A.; Jourdan, Fred; Danišík, Martin; Evans, Noreen (Elsevier BV, 2018)
Multi-method thermochronology applied to the northern Olympic Domain of South Australia reveals a complex thermal evolution with multiple thermal events. Apatite U/Pb (closure temperature ~550–350 °C) and muscovite 40Ar/39Ar ages (~400–350 °C) record post magmatic cooling from 1850 to 750 Ma for the ~1850 Ma Donington Suite, and from ~1560–1500 Ma for the ~1590 Ma Hiltaba Suite and the Gawler Range Volcanics. Potassium feldspar 40Ar/39Ar ages (~350–150 °C) record disturbed spectra that are likely related to hydrothermal alteration at ~1000–650 Ma in the Neoproterozoic Adelaide Rift Complex. Apatite fission track (~60–120 °C), zircon (U-Th-Sm)/He (~180–200 °C), and apatite (U-Th-Sm)/He (~45–75 °C) ages reveal regional low temperature thermal events at ~1000 Ma, ~430–400 Ma, 350–330 Ma, and ~200 Ma, in addition to localised thermal events during the Cretaceous. The ~1000 Ma apatite fission track ages are amongst the oldest recorded for South Australia and are only preserved near the margins of the Olympic Domain. The ~430–400 Ma and ~350–330 Ma cooling events are interpreted to be driven by the Alice Springs Orogeny. The Mesozoic thermochronometric ages are interpreted to record localised thermal perturbations, possibly related with hydrothermal activity within the northern Olympic Domain. The presence of abundant IOCG deposits near these young thermal anomalies may indicate that these zones record more favourable thermal conditions and/or exposure levels for IOCG discoveries in the study area.